Biometric Authentication Revolution: The Role of AI and UIDAI in Digital Payments - Kumar, Karrn; Sourabh, Swati; Kumar, Ashok; Kumar, Chandan; Kumari, Priya; Sharma, Anuradha; Amrendra, Kumar (International Journal of Research in Interdisciplinary Studies, 2025)
Although UPI and Aadhaar have revolutionized the payments environment in India, QR codes, mobile applications, cash, and cards continue to play a significant role in retail transactions. At the point-of-sale (POS), a novel dual-factor authentication payment method that combines a user PIN with an Aadhaar-linked fingerprint has been suggested in this paper. With this approach, the consumer only has to touch a verified fingerprint scanner at the merchant's terminal, input a PIN, and use India's Aadhaar infrastructure to settle the payment from account to account. This makes advantage of the current AEPS (Aadhaar Enabled Payment System) and NPCI rails to transfer money in real time from the payer's bank to the payee's bank and authenticate the user using UIDAI. In addition to discussing security, privacy, consent, and reliability issues, the paper describes the system architecture in depth, including biometric hardware, PIN input, UIDAI connection, and AI fraud analytics. This paper shows how a similar idea with common fingerprint sensors might be implemented in India by taking inspiration from China's palm-vein payment terminals. There are discussion of implementation issues such device pricing and rural connection. We contend that India's transition to a fully cashless, inclusive, and secure digital payment ecosystem might be accelerated by using this fingerprint+PIN strategy.